Francis Bacon and the Seventeenth-Century Intellectual Discourse - Funari, A. author. aut Link
XII, 174 p.
Keywords: This book explores the resistance of three English poets to Francis Bacon's project to restore humanity to Adamic mastery over nature, moving beyond a discussion of the tension between Bacon and these poetic voices to suggest theywere also debating the narrative of humanity's intellectual path.